E-Learning Adoption; How Is Students Behavior During The Covid-19 Pandemic? - Sehabuddin, Ahmad; Oktarina, Nina (Dinamika Pendidikan, 2022)
This study aims to analyze the factors that influence the acceptance and behavior of using e-learning students of the Faculty of Economics, Universitas Negeri Semarang during Covid 19. This study adopted five elements that make up the modeling of UTAUT 2. This study is a quantitative study. The sample in this study were 351 students and used a questionnaire in data collection. The data analysis technique used Structural Equation Models. The results of this study reveal that performance expectancy, hedonic motivation, and habit directly affect the behavioral intentions of students in using e-learning. Habit and behavioral intentions have a direct effect on student behavior in using e-learning. Performance expectancy, hedonic motivation and habit indirectly influence user behavior through students' behavioral intention in using e-learning. Habit is the variable that most plays a role in explaining student behavior in adopting e-learning when compared to other variables in this study. The conclusion of this study is that performance expectations, hedonic motivation, habits and behavioral intentions determine student behavior in adopting e-learning during Covid 19.